2018
DOI: 10.22159/ajpcr.2018.v11i1.22022
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Potential of Different Parts of Bogor Pineapple (Ananas Comosus [L.] Merr. Var. Queen) Cultivated in West Java-Indonesia

Abstract: Objective: The aims of this research were to observe antioxidant activities from different parts of Bogor pineapple (Ananas comosus [L.] Merr. Var. Queen) using two antioxidant testing methods which were 2,2-diphenyl-1-picrylhydrazyl (DPPH) and ferric reducing antioxidant power (FRAP) and correlation of total phenolic and flavonoid contents with their inhibitory concentration 50% (IC 50 ) of DPPH and exhibitory concentration 50% (EC 50 ) of FRAP.Methods: Each sample was extracted by reflux using different pola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…At present, there are no publications regarding the antioxidant activity of PCE. The study from Fidrianny et al 16 that conducted antioxidant assay of the peel, flesh and bractea of pineapple fruit showed that the antioxidant activities of the peel, flesh, and bractea are very strong. The IC 50 value from fruit flesh and the peel extract from Bogor showed a value below 50 ppm.…”
Section: Discussionmentioning
confidence: 99%
“…At present, there are no publications regarding the antioxidant activity of PCE. The study from Fidrianny et al 16 that conducted antioxidant assay of the peel, flesh and bractea of pineapple fruit showed that the antioxidant activities of the peel, flesh, and bractea are very strong. The IC 50 value from fruit flesh and the peel extract from Bogor showed a value below 50 ppm.…”
Section: Discussionmentioning
confidence: 99%
“…Ananas comosus é uma planta nativa da América do Sul e domesticada antes da chegada de Cristóvão Colombo em 1493 [103] . As substâncias fenólicas conferem propriedades antioxidantes e antimicrobianas [104][105][106] . Além disso, o caule e o fruto são ricos em proteases, conhecida como bromelina.…”
Section: Phyllanthusunclassified
“…The IC 50 values of the aqueous extracts from the various parts of breadnut and breadfruit ranged from 80 to 346 mg L −1 (Figure 2). Based on the DPPH assay IC 50 category of strong (50-100 mg L −1 ), moderate (101-150 mg L −1 ), and weak (>150 mg L −1 ) antioxidants (Fidrianny et al, 2018), especially the aqueous extracts of breadnut seed and breadnut leaf displayed strong radical scavenging activity, while the breadfruit leaf, breadnut fruit peel, and breadfruit fruit peel were considered to have moderate radical scavenging activity. This result was comparable to the Artocarpus heterophyllus leaves aqueous extracts where IC 50 values were 73.5 mg L −1 (Loizzo et al, 2010) while the methanolic extracts of A. heterophyllus fruit pulp were in the range of 400-700 mg L −1 .…”
Section: Determination Of Antioxidant Activitymentioning
confidence: 99%